2018
DOI: 10.1111/clr.13285
|View full text |Cite
|
Sign up to set email alerts
|

Thermal oxidation and hydrofluoric acid treatment on the sandblasted implant surface: A histologic histomorphometric and biomechanical study

Abstract: Adjunct HF acid application on the thermally oxidized surface did not provide an additional benefit compared to the sandblasted and acid-etched surface (SLA group).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 41 publications
1
6
0
Order By: Relevance
“…In the present study, the highest RTV was measured in the SLA group after healing of 3 weeks. This positive feature was observed in previous studies, in which SLA-surface implants achieved a high reverse torque resistance (mean 49.84 and 115.2 N/cm after 3- and 6-week healing, respectively) in the early stages of osseointegration [ 18 , 24 ]. It was remarkable that the B-coated surface group (BC) characterized by a lower spatial and hybrid surface roughness demonstrated the lowest early term RTV in this study.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…In the present study, the highest RTV was measured in the SLA group after healing of 3 weeks. This positive feature was observed in previous studies, in which SLA-surface implants achieved a high reverse torque resistance (mean 49.84 and 115.2 N/cm after 3- and 6-week healing, respectively) in the early stages of osseointegration [ 18 , 24 ]. It was remarkable that the B-coated surface group (BC) characterized by a lower spatial and hybrid surface roughness demonstrated the lowest early term RTV in this study.…”
Section: Discussionsupporting
confidence: 81%
“…Bone-to-implant contact (BIC%) and removal torque value (RTV) were designated as the primary outcomes, and relevant data were obtained from similar previous studies [ 18 , 19 ]. The power of the study was expressed as 1–β (β = probability of type II error), and an effect size of 1.978 and 1.484 was found for the BIC% and RTV, respectively.…”
Section: Methodsmentioning
confidence: 99%
“…The iliac crest site offers the advantages of bone characteristics, the absence of postoperative morbidity, and the ability to conduct a high number of implants test simultaneously; however, although the iliac crest exhibits low bone density, the cortical is thicker relative to the thin cortical of the posterior region of the maxilla, which also shows low bone density. Previous studies- 30,33,36,45 that used sheep models have reported that the animals were euthanized at the end of the experiments; in our study, all animals were kept alive and healthy. The insertion torque value is a direct measure of the bone's cutting resistance during implant insertion surgery.…”
Section: Dovepressmentioning
confidence: 81%
“…43 Previous studies of dental-implant designs and surface have used sheep, 30,[33][34][35][36]45 rabbits, 4,20,46 and dogs [47][48][49] as animal models. The most used sites in these animals are the jaw 47,48 or tibia 49 in dogs; the tibia 4,20,46,50 in rabbits; and the tibia, 34,35 iliac crest, 30,33,36,45 and mandible 51 in sheep. The iliac crest site offers the advantages of bone characteristics, the absence of postoperative morbidity, and the ability to conduct a high number of implants test simultaneously; however, although the iliac crest exhibits low bone density, the cortical is thicker relative to the thin cortical of the posterior region of the maxilla, which also shows low bone density.…”
Section: Dovepressmentioning
confidence: 99%
“…This in vivo study on low-density bone used the sheep iliac crest model for implantation, which is suitable for biomedical research due to its similarities to humans in weight, joint structure, bone tissue, and bone regeneration [ 16 , 22 ] and advantages over other experimental animal models in bone composition, metabolism, remodeling, and regeneration time [ 22 ]. Previous studies of dental implant designs and surfaces have used sheep [ 19 – 21 , 23 , 24 ], rabbit [ 7 , 25 , 26 ], and dog [ 27 29 ] models. The most commonly used sites in these animals are the mandible [ 27 , 28 ] and tibia [ 29 ] in dogs, the tibia [ 4 , 7 , 25 , 26 ] in rabbits, and the tibia [ 5 , 23 ], iliac crest [ 19 – 21 , 24 ], and mandible [ 30 ] in sheep.…”
Section: Discussionmentioning
confidence: 99%